Pengaruh Pupuk Organik dan Jarak Tanam Terhadap Pertumbuhan dan Hasil Padi pada Budidaya Metode SRI - Odang Hidayat (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2011)
This experiment was aimed to know the interaction between organic fertilizer and planting distance to growth and yield of rice cultivation with SRI method cultivation conducted in Gunungmanik Village Tanjungsari Subdistrict, Sumedang Regency, the experiment started from December 2009 until April 2010. The experiment design used was Plan of Plot Divided, with 12 treatment combinations consisting of the main plot of organic fertilizer (a1 = chicken manure a2 = sheep manure, and a3 = compost of market waste). The subplot is plant spacing (b1 = 25 cm x 25 cm, b2 = 30 cm x 30 cm, b3 = 60 cm x 30 cm x 30 cm, and b4 = 60 cm x 30 cm x 15 cm). experimental results show the interaction between organic fertilizer and plant spacing on growth and yield of rice on the cultivation of SRI method. The use of plant spacing of 60 cm x 30 cm x 15 cm, followed by provision of 10 tons ha-1 chicken cage gave the best growth against the number of tillers, the number of productive panicles per clump, the weight of 100 grains, and the weight of dry grain harvest per plot. The use of 60 x 30 x 15 spacing followed by 10 tons ha-1 chicken farming and 60 x 30 x 15 plant spacing followed by market composting of 10 tons ha-1, yielded the highest dry harvest grain.